From nanopowders to functional materials : proceedings of Symposium G, European Materials Research Society Fall Meeting, Warsaw University of Technology, 6th-10th September, 2004 - Piticescu, Radu Robert; Łojkowski, Witold; Blizzard, John R. (Diffusion and defect data. Solid state phenomena, 2005)
Research and development in the whole area of nanomaterials, including thin films, nanowires, nanocrystals, nano-composites and nanostructured bulk materials, continues to increase year by year. More and more attention is being focused on research which will permit greater control of structures at the nanometer level, in order to ensure that the desired functional properties can be obtained. The aim of the present book was to enable those working at the cutting-edge of research to present and debate the progress currently being made, in the theory and application, of functionalised nanoparticles within a multidisciplinary forum. The papers cover the topics: applications of functional materials, as based upon their mechanical, catalytic, electronic, optical and photonic properties; atomic and transport properties; electrical, magnetic and ferroelectric properties - as well as biocompatibility. This very useful collection of state-of-the-art papers constitutes an invaluable springboard to creating the nanotechnologies of tomorrow.